2020
DOI: 10.4081/ija.2020.1623
|View full text |Cite
|
Sign up to set email alerts
|

Wheat straw mulch improves summer maize productivity and soil properties

Abstract: Crop residue mulch in agricultural systems preserves soil health and improves crop productivity through its moderating influence on soil temperature regime and enhanced moisture retention. Therefore, a field experiment was conducted to determine the changes in soil properties and grain yield of irrigated summer maize in response to wheat straw mulching in the Northern maize region in China. The treatments investigated were: (i) application of wheat straw mulch (5000 kg ha-1) and (ii) no-mulch application (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In the year 2020, the best moisture maintenance was observed under mulch which fully covered the soil. Similarly, Noor et al (2021) found mulch to increase soil moisture measured gravimetrically in a soil layer of 0-15 cm of 2.5% under mulch in comparison with no-mulch treatment. Therefore, the mulch covering soil from 90-100% should be mainly in dry years recommended to maintain soil moisture.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In the year 2020, the best moisture maintenance was observed under mulch which fully covered the soil. Similarly, Noor et al (2021) found mulch to increase soil moisture measured gravimetrically in a soil layer of 0-15 cm of 2.5% under mulch in comparison with no-mulch treatment. Therefore, the mulch covering soil from 90-100% should be mainly in dry years recommended to maintain soil moisture.…”
Section: Resultsmentioning
confidence: 79%
“…Reducing the intensity of tillage or better soil at an undisturbed state and mulch cover significantly reduced soil warming, which is important for reducing water evaporation from soil and SOM mineralisation. Noor et al (2021) showed that wheat mulch decreased daily soil temperatures by 1.9 °C and 1.5 °C on average in 0-15 cm and 15-30 cm soil layers, increased soil moisture and the end improved also yields of the following crop. The soil temperature decreased in the following order: chiselling to 10-12 cm << shallow chiselling < stubble ≤ mulch and reflected the straw cover 10-15% under chiselling to 10-12 cm, 30-40% under shallow chiselling, 80-90% under stubble and 90-100% under mulch.…”
Section: Resultsmentioning
confidence: 98%
“…The concentrations of N in the straw and grain of maize were measured in each plot, using the Dumas method on the hand-harvested samples. The N-uptake and nitrogen use efficiency (NUE) were calculated by the formula of Wolf [ 59 ]. …”
Section: Methodsmentioning
confidence: 99%
“…The incorporation of crop residues in maize-based cropping systems is considered among the main practices regulating biological drivers of soil C cycling (Shahbaz et al, 2017;Noor et al, 2021) and promoting SOC sequestration (Zhang et al, 2021;Hao et al, 2022), whilst maintaining adequate grain or silage maize yields (Pittelkow et al, 2015). Furthermore, there is a synergy between crop residue incorporation and long-term organic fertilizers application, which can contribute to an increase in soil C pools and soil biological activities (Cui et al, 2018), thus leading to an overall improvement of soil fertility and agroecosystem sustainability (Bolinder et al, 2020).…”
Section: Highlightsmentioning
confidence: 99%